Fenomena Kotak Kosong dalam Pemilihan Kepala Daerah 2024 Berdasarkan Perspektif Politik Hukum - Arikatul Firdaus; Mohammad Fais (Jurnal Hukum Lex Generalis, 2024)
The phenomenon of empty boxes in regional elections that has occurred since 2015 and has increased in 2024 indicates a political system that tends to be pragmatic and undemocratic. Regional elections that should be carried out on the basis and aim of realizing effective regional government, institutionalizing and deepening local democracy are now ineffective in the elections that are carried out. Democracy, which has a classic meaning for government where the highest power is in the hands of the people, is now being misused for political interests alone. The existence of elections, regional elections that often result in the phenomenon of single candidates or so-called empty boxes in the implementation of elections which are considered as one form of representation of the people in choosing other than candidate pairs, but what happens is not as it should be. the public does not have the freedom to judge between empty boxes and candidate pairs only because of political interests that tend to be pragmatic in the name of the people.